Entropy Scaling for Viscosity of Pure Lennard-Jones Fluids and Their Binary Mixtures - Nguyen, The; Khennache, Samy; Galliero, Guillaume; Tran, Tuong; Tuong , Luc; Nguyen, Phuc; Hoang, Hai; Ho, Hieu Khac (Communications in Physics, 2022)
In this work, entropy scaling approaches for viscosity of pure Lennard-Jones (LJ) fluids and their mixtures have been investigated. To do so, we have employed reliable viscosity database available in literature for the pure LJ fluids, and performed the molecular dynamics simulation to generate viscosity database over a wide range of thermodynamic condition for the LJ mixture fluids. It has shown that for the pure LJ fluid, the entropy scaling approaches using the macroscopic properties for the reduction of viscosity yield noticeably better collapse of data than the one using the zero-density viscosity in the dense fluid region. In addition, we have developed viscosity correlations based on these approaches. It has been obtained that the correlations of macroscopic properties approaches predict the pure LJ fluid viscosity with average absolute deviation of around 4% more coming from the low-density states, whereas it is of around 8.50% more coming from the dense states for the other one. Finally, the viscosity correlations have been applied to the LJ mixtures. Interestingly, the correlations of macroscopic properties approaches are able to provide good estimations for all mixtures studied. However, it deteriorates for the viscosity of dense mixtures when the other employed.